Pengaruh Rasio Kemandirian Keuangan Daerah dan Rasio Efektivitas Pendapatan Asili Daerah Terhadap Belanja Modal - Nuraeni, Siti; Nurhasanah, Nunung; Kosasih, Kosasih (Gorontalo Accounting Journal, 2024)
Regional financial performance provides an overview of regional capacity in financial management. For six years, from 2018 to 2023, this research was conducted in Karawang Regency. The aim of this research is to determine and assess the influence of capital expenditure in Karawang Regency on the PAD Effectiveness Ratio and Regional Financial Independence Ratio from 2018 to 2023. One aspect of the methodology used in quantitative research is multiple linear regression testing. The research results show that the regional financial independence ratio influences the capital expenditure variable. The PAD effectiveness ratio has no influence on capital expenditure. Simultaneously, the regional financial independence ratio variable and the PAD Effectiveness Ratio variable influence capital expenditure.